Uso do território, experiências inovadoras e sustentabilidade: um estudo em unidades de produção familiares de agricultores/as na área de abrangência do Programa PROAMBIENTE, Nordeste Paraense - OLIVEIRA, José Sebastião Romano de (2006)
This study it evaluated the sustainability of the innovative experiences using indicator and criteria based on scientific theory the perception of peasants in the Irituia, São Domingos do Capim, Concordia do Pará and Mãe do Rio counties in an area encompassing the Polo Rio Capim, the PROAMBIENTE program. The objective was understand the daily of those social actors on the land using less stressful technologies on the environment and the reasons that led them to extend the traditional home garden or yards for other parcels of the Units of Familiar Production (FPU), turning them into Agroforest Systems (AFs). Questionnaire was applied and empirical data were collected, as well as interaction took place with the people involved in 78 FPUs allowing of variability indntification for Factor Analysis, establishing four factors of production and commercialization; production practices; intervention and gender questions. The first factors was used as criterium and requiring the return of the surveyor to 18 FPUs to apply the questionnaire and evaluation forms on the social, economic, cultural and environmental-ecological indicators. The sustainability evaluation was done by means of grouping these indicators using the Ameba agroecological method and by mapping using the interpolation method next door neighbor in the study area. Cultural and ecological/environmental indicators led to better conditions in terms of sustainability, in the range of good to excellent while the social economic indicators led to results appraised as weak to fair.